Current state and challenges of full-scale membrane bioreactor applications: A critical review. (January 2019) - Xiao, Kang; Liang, Shuai; Wang, Xiaomao; Chen, Chunsheng; Huang, Xia
Graphical abstract: Highlights: The pros, cons and progress in full-scale MBR application are summarized. Statistics on capital and operating costs of MBR are provided and compared with CAS. Efficiencies in treatment of ordinary and emerging pollutants are reviewed. Long-term operation stability is discussed in relation to membrane fouling. Future challenges of MBR application are outlined from multiple perspectives. Abstract: Membrane bioreactor (MBR) technology for wastewater treatment has been developed for over three decades. Our latest survey shows that MBR applications for wastewater treatment are still in rapid growth today. This review summarizes the pros, cons and progress in full-scale MBR applications. Critical statistics on the capital cost, operating cost, footprint, energy consumption and chemical consumption of full-scale MBRs are provided, and are compared to those of conventional activated sludge (CAS) processes with/without tertiary treatment. The efficiencies in full-scale treatment of ordinary pollutants (C, N and P), pathogens (bacteria and viruses) and emerging pollutants (e.g., trace organic pollutants) are reviewed. The long-term operation stability of full-scale MBRs is also discussed with several examples provided, with special attention placed on the seasonal variation of membrane fouling. Finally, the future challenges of MBR application are outlined from the perspectives of fouling control, pollutant removal, cost-effectiveness and competitiveness in specific fields of application.